Teaching blind women about the anatomy and physiology of the female reproductive system through educational manual - Mariana Gonçalves de Oliveira; Aline Cruz Esmeraldo Áfio; Paulo Cesar de Almeida; Márcia Maria Tavares Machado; Ana Cristina Lindsay; Lorita Marlena Freitag Pagliuca
Abstract Objectives: to evaluate blind women's learning on the anatomy and physiology of the female reproductive system through the use of an educational material. Methods: methodological development study performed with blind women. The participants responded the pre-test to evaluate their knowledge on sexual and reproductive health and received a manual on anatomy and the reproduction of the physiology After an individual reading, in a period ranging from three to fifteen days, they responded the post-test. Results: there was an increase of correct answers in the post-test in all the items in relation to the categories of The Woman's Body and How One Gets Pregnant becoming significant in the following knowledge of "clitoris increases with the woman excited" (p=0.009), "the function of the vagina in a sexual intercourse "(p<0.001), "How does fertilization occurs"(p<0.001) and "the ovulating period" (p<0.001). Conclusions: the manual enabled the participants to learn about the female anatomy and the physiology of fertilization after educational assistive technology.